Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fnins.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Driven Single Unit Activity From Micro-Electrocorticography

Abstract: High-fidelity measurements of neural activity can enable advancements in our understanding of the neural basis of complex behaviors such as speech, audition, and language, and are critical for developing neural prostheses that address impairments to these abilities due to disease or injury. We develop a novel high resolution, thin-film micro-electrocorticography (micro-ECoG) array that enables highfidelity surface measurements of neural activity from songbirds, a well-established animal model for studying spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…1D; Supplementary Video 1). (Wilks et al 2011;Sessolo et al 2013;Khodagholy et al 2015Khodagholy et al , 2016Khodagholy et al , 2017Cellot et al 2016;Kaiju et al 2017;Hermiz et al 2020). Some of these events (which we call Type 1 events) were similar in kinetics to single units (i.e., individual spikes) recorded with extracellular electrodes including prior surface PEDOT:PSS electrode recordings ((Khodagholy et al 2015((Khodagholy et al , 2016((Khodagholy et al , 2017 Fig.…”
Section: Pedot:pss Electrodes Record Neural Activity From the Surfacementioning
confidence: 84%
See 2 more Smart Citations
“…1D; Supplementary Video 1). (Wilks et al 2011;Sessolo et al 2013;Khodagholy et al 2015Khodagholy et al , 2016Khodagholy et al , 2017Cellot et al 2016;Kaiju et al 2017;Hermiz et al 2020). Some of these events (which we call Type 1 events) were similar in kinetics to single units (i.e., individual spikes) recorded with extracellular electrodes including prior surface PEDOT:PSS electrode recordings ((Khodagholy et al 2015((Khodagholy et al , 2016((Khodagholy et al , 2017 Fig.…”
Section: Pedot:pss Electrodes Record Neural Activity From the Surfacementioning
confidence: 84%
“…We detected a series of different 'fast' waveforms in recordings with PEDOT:PSS electrodes filtered between 250 and 6000 Hz. Previous studies with these devices have demonstrated recordings of single action potentials from the pial surface of various preparations, including in humans (Wilks et al 2011;Sessolo et al 2013;Khodagholy et al 2015Khodagholy et al , 2016Khodagholy et al , 2017 28 Cellot et al 2016;Kaiju et al 2017;Hermiz et al 2020). Some of these events (which we call Type 1 events) were similar in kinetics to single units (i.e., individual spikes) recorded with extracellular electrodes including prior surface PEDOT:PSS electrode recordings ((Khodagholy et al 2015((Khodagholy et al , 2016((Khodagholy et al , 2017) Fig.…”
Section: Pedot:pss Electrodes Record Putative Spiking Activity From the Surface Of The Human Brainmentioning
confidence: 91%
See 1 more Smart Citation
“…Doing so with recordings from the superficially located nucleus HVC enables accessibility by less invasive micro-electrode arrays, capable of resolving not only LFP, which has been shown suitable for BMI, 41 but also SUA and MUA. 1,3,[40][41][42]58,59 This provides a novel tool for probing the neural circuits underlying the production, acquisition, and maintenance of vocal communication signals and unlocks access to new models and experiments directed at understanding how neuronal activity is transformed into natural action and how peripheral effectors shape the neural basis of action. 22,54 Our approach also provides a proving ground for vocal prosthetic strategies.…”
Section: Exploiting Temporal Structurementioning
confidence: 99%
“…1b) arrays, placed on the surface of the CNS, or intracortical probes (Fig. 1c-e) should be adopted [12][13][14][15] . Indeed, extracellular electrodes are the most viable interfaces to record LFPs at high spatialtemporal resolution and high signal-to-noise ratio [16] , action potentials (spikes) from a population of nearest neurons ("multi-unit" recording), and in some instances also from single neurons (single-unit activity) [11,17,18] .…”
Section: Neural Interfaces For Extracellular Recording and Stimulationmentioning
confidence: 99%